2021
DOI: 10.3389/fendo.2021.696121
|View full text |Cite
|
Sign up to set email alerts
|

Decreased piRNAs in Infertile Semen Are Related to Downregulation of Sperm MitoPLD Expression

Abstract: Currently, the molecular mechanisms underlining male infertility are still poorly understood. Our previous study has demonstrated that PIWI-interacting RNAs (piRNAs) are downregulated in seminal plasma of infertile patients and can serve as molecular biomarkers for male infertility. However, the source and mechanism for the dysregulation of piRNAs remain obscure. In this study, we found that exosomes are present in high concentrations in human seminal plasma and confirmed that piRNAs are predominantly present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Our previous study has found that the types and expression levels of piRNAs were significantly decreased in the seminal plasma of asthenozoospermia patients compared with those in fertile controls (Hong et al, 2016). We also confirmed that the loss-of-function of endonuclease MitoPLD, an essential protein that is required for the biogenesis of piRNA during spermatogenesis, could cause a severe defect of piRNA accumulation in spermatozoa (Hong et al, 2021). However, whether the decreased expression of piRNA could affect the sperm motility remains unclear.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our previous study has found that the types and expression levels of piRNAs were significantly decreased in the seminal plasma of asthenozoospermia patients compared with those in fertile controls (Hong et al, 2016). We also confirmed that the loss-of-function of endonuclease MitoPLD, an essential protein that is required for the biogenesis of piRNA during spermatogenesis, could cause a severe defect of piRNA accumulation in spermatozoa (Hong et al, 2021). However, whether the decreased expression of piRNA could affect the sperm motility remains unclear.…”
Section: Introductionsupporting
confidence: 79%
“…To confirm the expression levels of piR‐1207 and piR‐2107 in GC‐2spd(ts), we extracted RNA from spermatozoa, seminal plasma and GC‐2spd(ts), and qRT‐PCR was performed to measure the RNA expression levels of piR‐1207 and piR‐2107. In our previous research, it has been proved that piR‐1207 and piR‐2107 were highly expressed in human spermatozoa and seminal plasma (Hong et al, 2016; Hong et al, 2021). Compared with levels of piR‐1207 and piR‐2107 in human spermatozoa and seminal plasma, the result showed that piR‐1207 and piR‐2107 were also expressed in GC‐2spd(ts) (Figure 2a‐C), and the products of qRT‐PCR were confirmed by agarose gel (Figure 2D).…”
Section: Resultsmentioning
confidence: 97%
“…The most abundant piRNA clusters identified in our dataset include: hsa-0088, hsa-0175, hsa-0084, and hsa-0142 (genomic locations indicated in extended names, supplemental Table S2). piRNAs are www.nature.com/scientificreports/ primarily thought to function in germline protection and integrity, though they may also contribute to sperm motility and post-transcriptional regulation of protein-coding genes 55 . However, only 5% of reads mapped to piRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…The most abundant piRNA clusters identi ed in our dataset include: hsa-0088, hsa-0175, hsa-0084, and hsa-0142 (genomic locations indicated in extended names, supplemental table S2). piRNAs are primarily thought to function in germline protection and integrity, though they may also contribute to sperm motility and post-transcriptional regulation of protein-coding genes 54 . However, only 5% of reads mapped to piRNAs.…”
Section: Sequencing Results and Gene Mappingmentioning
confidence: 99%